What You Get is What You See: Other-Rated but not Self-Rated Leaders' Narcissistic Rivalry Affects Followers Negatively - Theresa Fehn; Astrid Schütz (Journal of Business Ethics, 2020)
Individuals with high levels of narcissism often ascend to leadership positions. Whereas there is evidence that narcissism is linked to unethical behavior and negative social outcomes, the effects of leader narcissism on an organization's most important resource—its employees—have not yet been studied thoroughly. Using theoretical assumptions of the Narcissistic Admiration and Rivalry Concept (NARC) and social exchange theories, we examined how leaders' narcissistic rivalry was related to follower outcomes in a sample of matched leaders and followers. Followers of leaders high in narcissistic rivalry reported less perceived supervisor support, lower quality leader-member relationships, lower performance-based self-esteem, and lower job engagement. These effects were only found when follower-rated leaders' narcissistic rivalry was used in the model but not when self-rated leaders' narcissistic rivalry was used as a predictor. This implies that the negative effects of leaders' narcissistic rivalry on followers are driven by the expression of narcissistic tendencies (i.e., destructive leader behavior). Leader development should thus focus on changing destructive leader behavior. We propose that leaders high in narcissistic rivalry can be motivated to make such changes by showing them that by hurting their followers, they will eventually undermine their own reputation and status. Furthermore, selection and promotion practices should incorporate objective measures to weaken the effects of narcissists' self-promotional tactics in these contexts and thus prevent people high in narcissistic rivalry from rising to leadership positions.
Keywords: 300; Leaders' narcissistic rivalry; Leadership; Narcissism; Narcissistic admiration and rivalry concept; Follower outcomes